Perbandingan Pola Rasio Morfometrik dan Karakteristik Habitat Dua Spesies Ikan Wild Betta Asal Pulau Belitung - Syarif, Ahmad Fahrul; Robin, Robin; Tiandho, Yuant; Gustomi, Andi (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The existence of Wild Betta fish in Belitung Island needs to be studied. This study aims to analyze the differences in the morphology of two species of Wild Betta fish from Belitung Island based on the morphometric characteristics and habitat of these fish. The method used in this research is quantitative descriptive. This research was conducted in freshwater located in Dukong Village, Simpang Pesak District, East Belitung Regency from May to June 2020. The fish samples obtained were 35 fish consisting of 20 Betta uberis fish and 15 Betta edithae fish. The data obtained were analyzed descriptively and presented in graphs or tables. The results showed that the comparison of the morphometric ratio patterns found in the two Wild Betta fish species differed specifically from several characters, including Total Length (PT), Body Length (PB), Tail Length (PE), and Head Height (TK). Meanwhile, based on the ratio of morphometric characters, there are 3 main characteristics, namely: 1) Tail Length (PE) (1.249); 2) Head Length (PK) (0.869); 3) Width Body I (LB-I) (1,126); 4) Head Length (PK) (0.816); 5) Body Width II (LB-II) (0.337); and 6) Body Length (PB) (0.436). The habitat of Wild Betta fish from Belitung Island generally inhabits peat waters with fairly low pH conditions, ranging from 4-5 with the color of the waters that tend to be black to brownish.